Body optimization approach of sedan structure for improving small overlap impact rating. Issue 2 (4th March 2021) - Liu, Xi; Liang, Rui; Hu, Yuanzhi; Jiang, Chengyue; Tang, Xuebang; Bastien, Christophe
Abstract: Small overlap accidents of sedans often result in severe injuries. In this article, a crashworthiness design method, including engine-room energy management, suspension safety design and passenger compartment enhancement, was evaluated to improve the small overlap rating based on finite element simulation. Longitudinal reinforcement and shotgun redesign techniques were proposed to increase energy-absorption and decrease the impact force that transferred to the passenger compartment. The response surface methodology was utilized to propose the optimal passenger compartment parameters in order to reduce intrusion. The evaluation of the sedan structure performance was conducted by comparing simulated intrusion results with the rating guidelines of the Insurance Institute for Highway Safety (IIHS). The optimal results indicated that the intrusion was decreased by an average of 58.64%, with a minimum percentage of 44.98% around footrest area, and the measurement points for intrusion was upgraded to good. The proposed crashworthiness design approach is effective in vehicle structure optimization for better small overlap impact performance.